Assessment of the Social and Economic Structures of Semi-nomadic Communities in the Zirkuh Region Based on the Architecture of Seasonal Settlement Tenglia Aistrict with Ancient Anthropological Approaches - Enayatullah Dadman; Mukhtar Askari; Gulrahman Mushfiq; Wafiullah Aminzai (Randwick International of Social Science Journal, 2023)
Most information that are obtained from archaeological excavations includes only material data and non- material relationships, social behavior cannot be obtained solely from material data. For this purpose archeologists used ancient anthropological method, ancient anthropology is the study and investigation of contemporary lifestyles to enable archeologists to understand the processes by which archaeological evidence is created. Tanglia district is one of the semi-nomadic livestock of Zirkoh city in South Khorasan, This district has primitive architecture which is similar to pre-history, whose texture is like a small village and has private and public spaces, so the ancient anthropological study of this area was necessary. The present research has assisted and analyzed the relations within the establishment and the appearance of social structures of Tenglia district, regard to the research aria the social structure of the studied society was collected randomly and used described method, as a result geographical and environmental factors are important and necessary in the social structures of Tenglia district.